An in silico approach for identification of potential therapeutic targets for cancer treatment from celastrus hindsii Benth - Nguyen, Van Huy; Pham, Thanh Loan (Penerbit Universiti Kebangsaan Malaysia, 2024)
Celastrus hindsii Benth., a medicinal plant celebrated for its traditionally medicinal and practically therapeutic properties, has been used for generations in Vietnam to support the treatment of ulcers, tumors, and inflammation. The difference between several phenotypes, primarily identified as Broad Leaf (BL) and Narrow Leaf (NL), has been clarified by convincing scientific evidence through our previous proteomics study, which also revealed several bioactive proteins and peptides. Therefore, based on the findings, this study further investigated their therapeutic properties using a bioinformatics tool (BLASTP) and analyzing literature data. The results showed the distinguished variations in protein profile between the NL and BL proteomes and revealed five significant proteins with therapeutic properties. Of these, three proteins can have anti-tumor and anti-inflammatory activity and have been proven effective in cancer treatment. Therefore, C. hindsii, particularly the BL phenotype with elevated levels of therapeutic proteins, could be a promising plant candidate for future intensive research and applications for cancer treatment.